A guardiã e o guardião dos mistérios da alma: a incorporação de Exu e Pomba Gira como promotores da comunicação ego e self - Marian, Gislene Alves (2017)
The present work had as methodological clipping to demonstrate how the experience inside the religion Umbanda, most specifically the trance process, assists on the psychic development of their adepts. We aim to comprehend how the participation in this religion can promote potentials and complexes’ integration and, in addition, contributes to a communication between psychology and the Umbanda’s cosmovision. Particularly, a study was conducted regarding the symbolic representation of the entities Exu and Pomba Gira and its relation with Anima and Animus, both concepts inherent to analytical psychology, evaluating the scenario under the same theoretical perspective (from junguian matrix), and from the bias of post-colonial theory. Conducting a field research with six umbandists mediuns, we were able to corroborate the hypothesis saying that through the religious experience of trance the entities provide intimal contact with the unconscious during a psychic experience capable of establish a relation between ego and self. We also believe that by highlighting the psychosocial and religious dimension of Exu and Pombagira on mediun’s personal development and by presenting it as a religion that is intimately related with diversity and plurality of the Brasilian society, we could cooperate to overcome the persistent prejudice that rounds the religions from african’s matrixes and its practitioners, decreasing at least a little the incomprehension that is inherent to them